Tracking COVID-19 with wastewater to understand asymptomatic transmission. (July 2021) - Wannigama, Dhammika Leshan; Amarasiri, Mohan; Hurst, Cameron; Phattharapornjaroen, Phatthranit; Abe, Shuichi; Hongsing, Parichart; Rad, S.M. Ali Hosseini; Pearson, Lachlan; Saethang, Thammakorn; Luk-in, Sirirat; Kueakulpattana, Naris; Storer, Robin James; et al.
Highlights: This study provided the first dataset related to SARS-CoV-2 RNA in wastewater in Bangkok. A rise in SARS-CoV-2 RNA level in wastewater preceded an increase in clinical cases. Monitoring a virus in wastewater can help to better predict upcoming outbreaks. Our results provide powerful evidence of the importance of wastewater surveillance. Abstract: Introduction: SARS-CoV-2 RNA is excreted in feces of most patients, therefore viral load in wastewater can be used as a surveillance tool to develop an early warning system to help and manage future pandemics. Methods: We collected wastewater from 24 random locations at Bangkok city center and 26 nearby suburbs from July to December 2020. SARS-CoV-2 RNA copy numbers were measured using real-time polymerase chain reaction (PCR). Results: SARS-CoV-2 RNA was detected in wastewater from both the city center and suburbs. Except for July, there were no significant differences in copy numbers between the city center and suburbs. Between October and November, a sharp rise in copy number was observed in both places followed by two to three times increase in December, related to SARS-CoV-2 cases reported for same month. Conclusions: Our study provided the first dataset related to SARS-CoV-2 viral RNA in the wastewater of Bangkok. Our results suggest that wastewater could be used as a complementary source for detecting viral RNA and predicting upcoming outbreaks and waves.